Quality assessment of tuna and swordfish export products in the city of Santos, São Paulo : ingles - RODRIGUES, Yoly Gerpe; OLIVEIRA, João Paulo Ferreira Gonçalves de; HORA, Iracema Maria de Carvalho da; CALIXTO, Flávia Aline Andrade (Food Science and Technology, 2025)
The quality of fish can be evaluated by sensory, chemical, and microbiological analyses, with sensory analysis being the most important to determine the fish freshness. The aim of this study was to assess the factors that influence the quality and freshness of swordfish and tuna, as well as their signs of deterioration, to develop a sensory analysis protocol using the Quality Index Method. As it is a specific method, it was necessary to analyze the characteristics of each species. In the period between October 2021 and October 2022, 14,512 swordfish units and 1,534 tuna units, received and sold fresh by a fish warehouse, located in the city of Santos-SP, were analyzed. The Quality Index Method score developed for the swordfish ranged from 0 to 24, and for tuna, ranged from 0 to 34, where values close to zero indicate the best quality and fish freshness. Using the Quality Index Method, swordfish and tuna were classified into four quality ranges, making it possible to add value according to the fish classification. New physicochemical and microbiological studies can be carried out to certify the results obtained.